A Place at the Table: Organization Theory and Public Management. Issue 2 (20th March 2020) - Whitford, Andrew B; Milward, H Brinton; Galaskiewicz, Joseph; Khademian, Anne M
Abstract: In November 2018, the University of Arizona's School of Government and Public Policy hosted an international workshop on the role of organization theory in public management. The intention was to renew interest in organization theory in public management research. Scholars such as Herbert Simon, Herbert Kaufman, and Richard Selznick made seminal contributions to organization theory through the study of public organizations from the 1940s through the 1960s. In our estimation, organization theory is underrepresented in public administration scholarship for the last several decades. There are natural reasons for this trend, including the discipline's turn towards organizational behavior and the ascendancy of techniques that advance the study of large datasets and those that allow for experimental control. The recent emergence of "behavioral public administration" is a prominent example of this evolution. This symposium is an attempt to make a place at the table of public management for organization theory. The articles in this symposium contain articles from scholars who operate in the tradition of classic organization theory in new and innovative ways to lend intellectual purchase to studies of public organizations and public organizational networks.